JOB SATISFACTIONAND AFFECTIVE COMMITMENTAS PREDICTORS OF IN-ROLE BEHAVIOUR: A STUDY WITHIN THE MALAYSIAN HOTELINDUSTRY - NASURDIN, AIZZAT MOHD. (ITB Journal Publisher, LPPM ITB, 2006)
The purpose of this paper is to contribute to the knowledge of how job satisfaction (extrinsic and intrinsic satisfaction) and affective commitment influence in-role behaviour of nonsupervisory workers employed within the Malaysian hotel industry. The mediating role of affective commitment on the relationship between job satisfaction and in-role behaviour was also investigated. Regression analyses on the 188 responses collected demonstrated that both intrinsic and extrinsic job satisfaction had positive relationships with affective commitment. Specifically, intrinsic satisfaction was found to be more influential in explaining the variation in affective commitment. Additionally, affective commitment was found to have a significant and positive impact on in-role behaviour. The findings indicate that the two dimensions of job satisfaction were not significant predictors of in-role behaviour, thereby suggesting that the condition for the mediation effect of affective commitment was not supported. Implications of the findings to theory and practice are discussed. The paper concludes by identifying some possible limitations and offering suggestions regarding further investigations on in-role behaviour.